2019
DOI: 10.1002/slct.201903770
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Oxygen Exchange between CeO2 and O2: A Heteroexchange Mechanism

Abstract: Isotopic oxygen exchange (IOE) is a crucial reaction required in the purification of 238PuO2 which has been used as an important fuel in space exploration. Experimental studies on the IOE between 238PuO2 and O2 are costly and hazardous due to the radioactivity. With extremely similar crystal structures, CeO2 could be a fair surrogate for 238PuO2 in the investigation of physicochemical properties. Here, we perform density functional theory calculations to simulate the IOE between CeO2 and O2, wherein a heteroex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…On the other hand, it is generally well known that the molecular dissociation and gas-phase exchange of O 2 is energetically much more challenging, with theoretical calculations and experimental isotopic oxygen exchange measurements placing the activation energy over CeO 2 around 1.1 eV 39 , 40 . Hence, here we speculate that the observed fluxional behavior is associated with the energetically more facile steps of lattice oxygen abstraction by CO, and that the absence of measurable conversion is due to the lack of oxygen vacancy back-filling from molecular O 2 exchange.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it is generally well known that the molecular dissociation and gas-phase exchange of O 2 is energetically much more challenging, with theoretical calculations and experimental isotopic oxygen exchange measurements placing the activation energy over CeO 2 around 1.1 eV 39 , 40 . Hence, here we speculate that the observed fluxional behavior is associated with the energetically more facile steps of lattice oxygen abstraction by CO, and that the absence of measurable conversion is due to the lack of oxygen vacancy back-filling from molecular O 2 exchange.…”
Section: Resultsmentioning
confidence: 99%
“…CeO 2 , one kind of rare earth oxide, exhibits outstanding redox properties, as it possesses a redox couple of Ce 4+ /Ce 3+ with low redox potential, which can be mutually converted under redox conditions [29, 30] . So far, CeO 2 has been used widely as a hydrogen storage material, oxygen storage material, gasoline catalyst, and so on [31–33] .…”
Section: Introductionmentioning
confidence: 99%
“…CeO 2 ,o ne kind of rare earth oxide, exhibits outstanding redox properties, as it possesses ar edox couple of Ce 4 + /Ce 3 + with low redoxp otential, which can be mutually converted under redox conditions. [29,30] So far,C eO 2 has been used widely as ah ydrogen storage material, oxygen storage material, gasoline catalyst, and so on. [31][32][33] However,i ts application in the HER and OER has been limited.R ashid et al [34] reported at ernary composite of graphitic carbon nitride, CeO 2 ,a nd Fe 3 O 4 as an alkalineH ER and OER catalyst for the first time, demonstrat-ing that the synergistic effect between CeO 2 and Fe 3 O 4 dramatically enhances the catalytic property.T hus, the design and synthesis of at ransition metal oxide/CeO 2 catalystf or the HER and OER in alkaline surroundingsi sm eaningful.…”
Section: Introductionmentioning
confidence: 99%